Pengaruh Kemiringan Talang Terhadap Pertumbuhan Tanaman Caisim (Brassica chinensis L var. parachinensis) dengan Menggunakan Sistem Hidroponik NFT (Nutrient Film Technique) - sembiring, julian; Rumambi, David P.; Rantung, Ruland A. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
Gutter slope is a crucial aspect of hydroponic systems, especially the nutrient film technique (NFT), which directly affects the flow of nutrient solution and plant root health. A proper slope ensures even nutrient flow throughout the gutter, providing equal access for each plant root to absorb nutrients and oxygen. The gutter slope, measured in percent, is derived from the length of the horizontal gutter. The purpose of this study was to gain a deeper understanding of the NFT (nutrient film technique) hydroponic system, particularly the slope of the gutter, and to analyze its potential applications. Three different slopes (T) were used in this study: (T1 = 6%, T2 = 9%, T3 = 12%).The study demonstrated the greatest plant growth at a 12% slope, with the highest plant height of 38.75 cm, an average root length of 35.3 cm, and an average fresh weight of 84.6 grams. However, the highest number of leaves was achieved at a 9% slope. Generally, a 12% slope yields the best results, with plant weight and height being crucial for production.